Glass Ceiling dalam Profesi Akuntan: Menyingkap Hambatan Tak Terlihat - Astriayu Widyari, Nyoman Yudha; Ida Ayu Komang Tiara Pratistha Sari; Putu Ayu Diah Widari Putri (Akubis : Jurnal Akuntansi dan Bisnis, 2025)
The glass ceiling phenomenon is an invisible barrier that limits women in achieving leadership positions, including in the accounting profession. Although women's participation in the workforce has increased, they still face gender bias, social stereotypes, discrimination based on preferences, and dual role pressures. This study aims to examine in more depth the causes and impacts of the glass ceiling phenomenon in the accounting profession through a cross-continental literature study approach. Using Gender Role Theory, it was found that social norms attached to women's traditional roles contribute greatly to negative perceptions of their leadership abilities. Meanwhile, the theory of Socialist Feminism explains that gender inequality in the workplace is the result of a system of capitalism and patriarchy that limits women's access to power and strategic positions. The discussion in this article shows that in various regions, including Africa, Asia, Europe, and America, patriarchal organizational structures and cultures are still the main barriers to women's career advancement. These results emphasize that the glass ceiling is not an individual obstacle, but a systemic phenomenon that needs to be addressed through inclusive policies, structural organizational reforms, and more gender-equitable social awareness.